2 - Memory and disenchantment in Nadine Gordimer’s None to Accompany Me and Zoe Wicomb’s Playing in the Light - Zuhmboshi Eric Nsuh (African Sociological Review, 2015)
The aim of this paper is to show how Nadine Gordimer, in None to Accompany Me and Zoe Wicomb, in Playing in the Light have represented the past in their post-Apartheid novels and how it has influenced the ontological situation of the characters in the above texts in question. This paper is, therefore, based on the premise that the behaviour and present conditions of the characters in the works of the above novelists have been shaped by the trauma of their past. It is for this reason that the characters look at the past with anger and acrimony against those who perpetrated acts of nefariousness against them.